Search for associated Higgs boson production WH→WWW *→l±νl′±ν′+X in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We present a search for associated Higgs boson production in the process pp̄→WH→WWW*→l±νl′±ν′ +X in final states containing two like-sign isolated electrons or muons (e±e±, e±μ±, or μ±μ±). The search is based on D0 run II data samples corresponding to integrated luminosities of 360-380pb-1. No excess is observed over the predicted standard model background. We set 95% C.L. upper limits on σ(pp̄→WH) ×Br(H→WW*) between 3.2 and 2.8 pb for Higgs boson masses from 115 to 175 GeV. © 2006 The American Physical Society.
Keywords: Higgs boson; Integrated luminosities; Data acquisition; Electrons; Lighting; Mathematical models; Luminescence